SARS-CoV-2 infection and stroke - Wan, Minying (American Journal of Translational Medicine, 2022)
Stroke is a disease that affects the arteries leading to and within the brain. It is the No. 5 cause of death and a leading cause of disability in the United States. It is a fatal morbidity that needs emergency medical admission and immediate medical attention. COVID-19 ischemic brain damage is closely associated with common neurological symptoms, which are extremely difficult to treat medically, and risk factors. We performed literature research about COVID-19 and ischemia in PubMed, and in published papers, we discovered a similar but complex pathophysiology of SARS-CoV-2 infection and stroke pathology. A patient with other systemic co-morbidities, such as diabetes, hypertension, or any respiratory disease, has a fatal combination in intensive care management when infected with SARS-CoV-19. Furthermore, due to their shared risk factors, COVID-19 and stroke are a lethal combination for medical management to treat. In this commentary, we discuss shared pathophysiology, adjuvant risk factors, challenges, and advancements in stroke-associated COVID-19 therapy.